PEMILIHAN ALAT KONTRASEPSI YANG TEPAT PADA PESERTA KB DENGAN MENGGUNAKAN METODE AHP (Analitical Hierarky Process) - Yosefa, Sonya (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Abstract: Determination of contraceptives requires several aspects of consideration that are mature and accurate. Due to the limited time and ability to see all aspects of accuracy, often causing errors in decision making. Therefore, a system is needed to determine the right contraception by taking into account the criteria existing aspect criteria. By implementing the Analytical Hierarchy Process (AHP) method and the Super Decisions software, the priority level of the desired variables can be assessed by creating a hierarchy of all existing variables. Comparing between each criterion and integrating it with the category assessment needed, will result in a decision to choose contraception from the predetermined criteria. With this decision support system designed, consumers can make decisions in choosing the right contraception. Keywords: Decision Support System (SPK), Analytical Hierarchy Process (AHP), Determine appropriate contraception